1996
DOI: 10.1002/(sici)1097-0215(19960529)66:5<664::aid-ijc14>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of involvement of CD44 in endothelial cell proliferation, migration and angiogenesisin vitro

Abstract: Angiogenesis is essential for tumor growth and metastasis. In the process of angiogenesis, the interaction between adhesive proteins of endothelial cells and extracellular matrix components plays an important role by mediating cell attachment, which is indispensable for their motility, and by transmitting the regulatory signals for cell locomotion and proliferation. In this study, we examined the hypothesis that CD44 expressed on the endothelial cell surface is involved in the angiogenesis process. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 195 publications
(119 citation statements)
references
References 19 publications
6
109
2
Order By: Relevance
“…The involvement of CD44 in tube formation of endothelial cells is also supported by data obtained by Trochon et al 20 The mechanism whereby CD44 isoforms exert their different biologic activities involves interactions with the cytoskeletal proteins ankyrin and the ERM family, as well as binding to signaling molecules such as Rho GTPase. 17,41 Interestingly, Stern and Csóka 10 have suggested that one of the multiple-splice forms of CD44 can interact with hyaluronidase.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…The involvement of CD44 in tube formation of endothelial cells is also supported by data obtained by Trochon et al 20 The mechanism whereby CD44 isoforms exert their different biologic activities involves interactions with the cytoskeletal proteins ankyrin and the ERM family, as well as binding to signaling molecules such as Rho GTPase. 17,41 Interestingly, Stern and Csóka 10 have suggested that one of the multiple-splice forms of CD44 can interact with hyaluronidase.…”
mentioning
confidence: 53%
“…16,17 Although several studies have reported the expression of CD44 on endothelial cells, 18,19 little is known about the physiologic significance of CD44 expression on these cells. 18,20 Hyaluronan turnover in humans is very rapid (in the blood stream its half-life is about 5 min and in skin about 1 day); the enzymes responsible for hyaluronan degradation, hyaluronidases, exist in several isoforms 21 and are broadly distributed. Overexpression of hyaluronidases have been reported in several tumors of aggressive character.…”
mentioning
confidence: 99%
“…Trochon et al (1996) found that antibodies to CD44 inhibit both endothelial-cell migration and proliferation, the suggestion being that endothelial-cell-associated CD44 is important in angiogenesis. It has been reported that cells from malignant human tumours, but not from normal tissues, express hyaluronidase (HAase) (Liu et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…34,35 This matrix has been used as an in vitro model to mimic closely the angiogenesis phenomenon since endothelial cells invade blood clots in the process of wound repair. 20,36 In this gel aggregates of endothelial cells organize themselves to form characteristic tubes that resemble blood capillaries. Pepper et al 20 have shown that bFGF induces capillary lumen formation in this model, demonstrating the direct effect of this factor in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%